Codex - Grossman, Lev (Orlando, Florida Harcourt, Inc., 2005)
About to depart on his first vacation in years, Edward Wozny, a hot-shot young investment banker, is sent to help one of his firm's most important and mysterious clients. When asked to uncrate and organize a personal library of rare books, Edward's indignation turns to intrigue as he realizes that there may be a unique medieval codex hidden among the volumes, a treasure kept locked away for many years and for many reasons. As friends draw Edward into a peculiar and addictive computer game, his obsession deepens as he discovers surprising parallels between the game's virtual reality and the mystery of the codex. An accomplished and entertaining thriller, Codex explores the mysterious power of books in the medieval and modern ages.
Cover title: Codex: a novel.
"A Harvest book."